Pembelajaran Ilmu Tajwid dalam Meningkatkan Kualitas Bacaan Al-Qur’an - Chalimatus Sa’dijah (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2021)
This paper defote to prove the importance of Ilmu Tajwid in the formation of standard guides and standards in the recitation of the Qur'an. Therefore, this paper seeks to answer a single problem: